THERMOELECTRIC TEC UNTUK MEMBANTU MENINGKATKAN MASSA OKSIGEN PADA PROSES PEMBAKARAN MOTOR BAKAR - Khalida, Zulfa; Rahmad, Hadi; Puspa Dewi, Yulia; Chandra, Kartika; Putranti, Eti (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2024)
This research was conducted to determine the effect of TEC or air cooling on the torque produced on a 110 cc motorbike. The TEC is connected to the intake manifold using a hose and the exhaust gas is connected to a gas sensor to see the Air Fuel Ratio AFR. This research shows the same results as the theory that decreasing air temperature can fertilize the fuel mixture, which is proven by a decrease in AFR of around 4.8% and this occurs The increase in power at 5600 rpm is 6.8 HP, around 1.8 HP higher than not using TEC.